HPV16 persistent infection and recurrent disease after LEEP - Bruno, Maria Teresa; Cassaro, Nazzario; Garofalo, Salvatore; Boemi, Sara (Virology journal, 2019)
About 23% of patients develop CIN2+ after LEEP treatment due to residual or recurrent lesions. The majority of patients with HPV infection were HPV negative before treatment, but 16,4% were still HPV 16 positive after treatment, indicating that conization do not necessarily clear HPV infection rapidly. The aim of this retrospective study was to evaluate the possible correlation existing between the appearance of recurring high-grade lesions and the viral genotype 16, and other risk factors such as residual disease. One hundred eighty-two HPV positive patients underwent LEEP for CIN2+. The follow-up post treatment was carried out every 6 months. Abnormal results during follow-up were confirmed histologically and considered recurrent high-grade intraepithelial cervical lesions (CIN2/CIN3 or CIS). Statistical analysis was performed by using the SPSS software package for Windows (version 15.0, SPSS, Chicago, IL, USA). Descriptive statistics are expressed as frequency, arithmetic mean, standard deviation (S.D.) and percentages. We calculated significance (P < 0.5) with the Easy Fischer Test. We calculated the Odds Ratio (OR) of women with peristent HPV 16 infection and positive margin, to have a recurrence. In our study, the rate of persistent infection from HPV 16, after LEEP, was 15.9% (29/182) with 94% (17/18) of the recurring disease occurring within 18 months of follow up. From this study it was found that the persistence of genotype 16 is associated with a greater rate of relapse post-conization of CIN 2+ lesions, with respect to other genotypes. Our study further supports those studies that demonstrate that the risk for residual disease or relapse is not to be overlooked, also when the margins are negative, but persistent HPV infection is present. In our case study, 40% of relapses were in women with negative margin, but with persistent HPV 16 infection. Even more so, the margins involved in HPV16 positive subjects is another prediction factor for relapse. Our results show the importance of genotyping and that persistent HPV 16 infection should be considered a risk factor for the development of residual/recurrent CIN 2/3.